2002
DOI: 10.1007/bf02376047
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial phenomena on the graphite-lithium electrode during the formation process and thermal aging

Abstract: International audienceSlow scan voltammery (SSV), electrochemical impedance spectroscopy (EIS) and galvanostatic cycling (GC) were used to characterize the formation of the Solid Electrolyte Interphase (SEI) on a graphite electrode during lithiation and delithiation and during thermal aging. The SSV and GC results show the irreversible character of the first reduction peak/semi-plateau at 0.8 V. After aging, a new irreversible plateau appears in the GC curves. Concomitantly the interfacial resistances as deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…However, experimental investigations based on independent thermodynamic, kinetic, and crystallographic measurements have recently questioned this two-phase process in this composition range. Anomalous behaviors and hysteresis between the battery charge (delithiation) and discharge (lithiation) have been observed in the entropy curve, , in the electrochemical impedance spectrometry measurements and in the crystallographic data . To figure out the origin of these experimental anomalies, we have investigated the phase diagram of Li x C 6 in the range 0.5 ≤ x ≤ 1.0, combining accurate first-principles calculations and statistical physics.…”
Section: Introductionmentioning
confidence: 96%
“…However, experimental investigations based on independent thermodynamic, kinetic, and crystallographic measurements have recently questioned this two-phase process in this composition range. Anomalous behaviors and hysteresis between the battery charge (delithiation) and discharge (lithiation) have been observed in the entropy curve, , in the electrochemical impedance spectrometry measurements and in the crystallographic data . To figure out the origin of these experimental anomalies, we have investigated the phase diagram of Li x C 6 in the range 0.5 ≤ x ≤ 1.0, combining accurate first-principles calculations and statistical physics.…”
Section: Introductionmentioning
confidence: 96%
“…35 From the analysis of entropy and crystal structure anomalies and impedance spectroscopy, Yazami and Reynier have fractional stages in the range of Li composition from 0.5 to 1.0. [36][37][38] Other authors have also found evidence for the existence of these stages by analyzing the effects of intercalation at low temperatures 39 or proposed their occurrence through DFT calculations. 19 On the other hand, the experimental visualization of the intermediate stages between stages I and II is very complex since, in addition to the contribution of the configurational energy (as presented here), there are also contributions due to excess energy that emerges as result of stress due to the deformation of graphite layers.…”
Section: Discussionmentioning
confidence: 99%